PENGARUH MEDIA INTERAKTIF BERBASIS APLIKASI NEARPOD TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH KELAS XI DI MA DARUL AMIN PALANGKA RAYA - Selvia, Selvia; Jasiah, Jasiah; Istiyati Mahmudah (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study focuses on the influence of interactive media based on the Nearpod application on student learning outcomes in the Fiqh subject of class XI at MA Darul Amin Palangka Raya, especially on the material of murder in Islamic law (jinayah). The approach used is quantitative with the type of Pre-Experimental One-Group Pretest-Posttest Design with a sample of 26 students. Data were obtained through multiple choice tests, observation, and documentation. The results of observations from the application of the Nearpod application media showed an increase from 84,8% in the first meeting (good category) to 97,8% in the second meeting (very good category), this increase reflects the increasing involvement and enthusiasm of students in participating in learning. The average student score also increased from 58,31 in the Pretest to 80,92 in the Posttest. The Shapiro-Wilk normality test showed that the data were normally distributed (significance of 0,090 in the Pretest and 0,059 in the Posttest > 0.05), while the paired sample t-test results obtained a significance value of 0,000 < 0,05, so that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Thus, it can be concluded that the interactive media based on the Nearpod application has an influence on student learning outcomes in the Fiqh subject of class XI at MA Darul Amin Palangka Raya.